Changes in the in-phase relationship between the Indian and subsequent Australian summer monsoons during the past five decades - J.-Y. Yu; M. A. Janiga; M. A. Janiga (Annales Geophysicae, 2007)
This study examines the decadal changes in the in-phase relationship between Indian summer monsoon and the subsequent Australian summer monsoon using observational data from 1950–2005. The in-phase relationship is the tendency for a strong Indian summer monsoon to be followed by a strong Australian summer monsoon and vice versa. It is found that the in-phase relationship was weak during the late 1950s and early 1960s, strengthened to a maximum in the early 1970s just before the 1976/77 Pacific climate shift, then declined until the late 1990s. Pacific SST anomalies are noticed to have strong persistence from boreal to austral summer, providing the memory to connect the Indian and subsequent Australian summer monsoon. The simultaneous correlation between the Pacific SST anomalies and the Indian summer monsoon is always strong. It is the weakening and strengthening of the simultaneous correlation between the Australian summer monsoon and the Pacific SST anomalies that contributes to the decadal variations of the in-phase monsoon relation. This study suggests that the interaction between the Australian monsoon and the Pacific Ocean is crucial to tropical climate variability and has experienced significant changes over the past five decades.